Pendampingan Remaja dalam Penyalahgunaan NAPZA di JakartaTimur - Erika Lubis; Aliana Dewi; Karim, Aminah; Sondang Manurung (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2025)
Substantial progress has been made in developing prevention programs for adolescent drug abuse. The most effective interventions target salient risk and protective factors at the individual, family, and/or community levels and are guided by relevant psychosocial theories regarding the etiology of substance use and abuse. This article reviews the epidemiology, etiologic risk and protective factors, and evidence-based approaches that have been found to be most effective in preventing adolescent substance use and abuse. Exemplary school and family-based prevention programs for universal (everyone in population), selected (members of at-risk groups), and indicated (at-risk individuals) target populations are reviewed, along with model community-based prevention approaches. Challenges remain in widely disseminating evidence-based prevention programs into schools, families, and communities